The Effect of Organizational Justice and Job Involvement on Turnover Intention with Job Satisfaction as an Intervening Variable - Deby Ayu Anggela; Dewi Andriani (Indonesian Journal of Law and Economics Review, 2022)
This study aims to determine the effect of organizational justice and job involvement on turnover intent with job satisfaction as an intervening variable at PT Aggiomultimex International Group Sidoarjo. This research uses quantitative research with hypothesis testing. The sample used in this study were 118 employees at PT Aggiomultimex International Group Sidoarjo. The analytical tool used in this study uses statistical software. This study aims to determine the effect of organizational justice, job involvement version 2.5.0. The main data in this study came from a questionnaire. The results of this study prove that (1) organizational justice has a significant effect on turnover intention (2) job involvement has a significant effect on turnover intention (3) Organizational justice variable has no effect on turnover intention (4) Job involvement variable has a significant effect on turnover intention (5 ) Job satisfaction variable has a significant effect on turnover intention (6) Organizational justice variable has no effect on turnover intention through job satisfaction (7) Job involvement variable has a significant effect on turnover intention through job satisfaction